STRATEGI PENGEMBANGAN TUNJUNGAN SEBAGAI DESTINASI MILENIAL - Vredy Agus Prasetio; I Dewa Gde Satrya; I Nyoman Sudiarta (JURNAL MASTER PARIWISATA, 2023)
This study aims to analyze the development strategy of Jalan Tunjungan, Surabaya City, as a millennial tourist destination. This research method was carried out with a descriptive qualitative approach, data collection methods through interviews and observations. The results of this study are the government has developed and collaborated with the private sector, the community, and business actors for tourism development on Jalan Tunjungan. The development was carried out by, first, rearranging, revitalizing, and repairing the existing corridors in the Jalan Tunjungan area to make it look neat. Second, the creation of Tunjungan Romansa branding to attract millennial tourists. Third, many contemporary food and beverage businesses have been established in Tunjungan with Alfresco Dining’s concept. Fourth, make art, cultural and historical events, such as Mlaku-Mlaku Nang Tunjungan and the tearing of the flag at Hotel Majapahit which is held every year. At every point along Jalan Tunjungan there is a space for artists to express their works of art. The conclusion of this study is Jalan Tunjungan area is suitable as a millennial tourist destination because it integrates modernity and heritage. Keywords: tourism development strategy; heritage tourism; millennials tourist.